The Synergistic Effects of ICT and Gamification on Reading Literacy in Primary Education - Ismail, Ismail (Universitas Muhammadiyah Enrekang, 2024)
This study investigates the synergistic effects of integrating Information and Communication Technology (ICT) and gamification on reading literacy among elementary school students. The aim was to evaluate how these innovative approaches can enhance reading skills, motivation, and engagement in a classroom setting. A mixed-methods design was employed, involving quantitative assessments of reading comprehension and vocabulary retention, alongside qualitative surveys capturing student experiences. The results indicate that students in the experimental group utilizing gamified ICT applications experienced significant improvements in reading comprehension and vocabulary retention, with a 41% increase compared to a mere 7% for the control group. Qualitative feedback revealed heightened motivation and engagement, supporting the notion that gamification fosters intrinsic motivation in learning. The findings underscore the potential of gamified ICT environments to enhance reading literacy and student engagement, providing valuable insights for educators and policymakers. Future research should focus on larger, diverse samples and longitudinal studies to further explore the effectiveness and sustainability of these innovative educational practices.